Epoxidation of indene and cyclooctene on nanocrystalline anatase titania catalyst - Ramaswamy, Veda; Awati, Preeti; Ramaswamy, A. V. (Topics in Catalysis, 2006)
Nanocrystalline anatase titania samples of different crystallite sizes were prepared by sol gel method using ultrasonication and calcination at different temperatures. The calcined samples were treated with H2O2 in order to study the role of surface hydroxyl groups present on titania in generating reactive oxygen species responsible for the epoxidation reaction. The crystallite size of the calcined samples increased from 4 to 18 nm as the calcination temperature increased from 473 to 773 K, respectively. More uniform distribution/dispersion of the nanoparticles (SEM), marginally higher surface area, better thermal stability and phase purity are some of the advantages of preparation of nanocrystalline TiO2 by using ultrasonication. EPR spectral data on the H2O2-treated samples confirmed the presence of superoxide radical species. The two distinct UV bands observed at 400 and 450 nm are assigned to charge transfer of peroxide (O-2 2-) to Ti. FT-IR spectral data show that the surface hydroxyl groups are the active sites in the generation of reactive oxygen species. The catalytic activity was evaluated in a series of epoxidation reactions using indene and cyclooctene as substrates and aqueous H2O2 as oxidant. The activity was found to decrease with increase in the calcination temperature of the samples, obviously due to an increase in crystallite size and a decrease in surface hydroxyl groups. The nanoparticle titania samples show better conversion and selectivity than the standard titania (Degussa P-25). The kinetic studies revealed that the reaction followed a pseudo first order kinetics in excess of H2O2.
19th Meeting of the North-American-Catalysis-Society (NAM), Philadelphia, PA, MAY 22-27, 2005
Keywords: cyclooctene epoxidation; epoxidation of indene; nanocrystalline anatase titania; superoxide radical on titania